Optimized CUT&RUN protocol for activated primary mouse B cells - Stormy E. Ruiz; Robert W. Maul; Patricia J. Gearhart (PLoS ONE, 2025)
ChIP-seq has long been the standard for study of chromatin-protein interactions. However, development of a new technique, CUT&RUN, showed substantial advantages compared to ChIP-seq including higher quality signal while using substantially less sample. While a powerful technique, the original protocol was designed using cell lines and histones as targets. Due to their fragility, this was unsuitable for obtaining high-quality data from activated primary B lymphocytes. To adapt this protocol for B cells, cells were fixed prior to nuclear isolation, and several critical adjustments were introduced to the procedure and reagents. We measured binding of H3K4me3 histone and RNA Polymerase II, detecting robust peaks with as little as 100k nuclei. Additionally, freeze-thaw of B cells prior to processing did not affect results, emphasizing the flexibility of this modified technique. Using the protocol described here will allow one to quantify non-histone proteins bound to DNA from limited numbers of B cells with more efficiency than can be achieved from the current standard, ChIP-seq.